Pengaruh ROE dan DER terhadap Harga Saham pada Perdagangan Eceran - Angeli, Putri; Meirisa, Faradila (Universitas Multi Data Palembang, 2025)
This research aims to evaluate the impact of Return On Equity and Debt To Equity Ratio on share prices within the retail trade sub-sector listed on the Indonesia Stock Exchange from 2019 - 2023. This study was conducted due to existing discrepancies with prior researchers. During the period from 2019 - 2023, the population consisted of 25 businesses listed on the Indonesia Stock Exchange within the retail trade sub-sector, using a purposive selection approach with a sample size of 125 companies. Processing data using the SPSS 26 program with the partial test results show that the ROE variable has a negative and has no significant influence on share price while the DER variable has a positive and has a significant influence on share price. Simultaneously ROE and DER have a significant effect to the share price that is equal to 5% while the rest 95% influenced by the other factor.